Statistical Analysis of the Effectiveness of Two Investment Multicurrency Portfolios in the Context of Various Cryptocurrencies - Fedorenko, A. V. (Statistics of Ukraine, 2024)
The current issue with the global currency system is its lack of stability, necessitating comprehensive reform in the context of changing global economic order. These changes are prompting a transformation of the existing system into a multicurrency one, focusing on currency polycentrism that arises due to global financial-economic crises and the redistribution of currency powers. Such a multicurrency system reflects the growing influence of various currencies and currency blocks, leading to a decrease in the dominance of traditional currency reserves like the US dollar and the euro. One of the main aspects of the reform is the inclusion of cryptocurrencies in international currency relations, which opens up new possibilities for diversifying investment portfolios and reducing currency risks. Cryptocurrencies such as Bitcoin, Ethereum, Solana, and BNB offer an alternative to traditional currencies that can help stabilize currency fluctuations thanks to their non-correlation with traditional financial systems. In this light, investors need to develop effective strategies for working in the highly volatile cryptocurrency market, which includes deep analysis of historical data, risk assessment, and evaluation of potential profitability. The proposed comprehensive approach is based on the statistical study of this data and the use of advanced financial models to predict future investment behavior. Considering two multicurrency portfolios composed of cryptocurrencies like Solana, BNB, and Ethereum, the study focuses on comparing their effectiveness through risk and profitability analysis. Special attention is given to the correlation relationship between assets, which allows investors to better understand the interconnections within their portfolios and optimize their structure according to changing market conditions. The study results confirm the hypothesis about a direct relationship between the level of risk and potential investment returns, highlighting the importance of a comprehensive approach to managing investment portfolios. The conclusions of the article point to significant prospects for further research of investment strategies, especially in the context of the development of the cryptocurrency industry, opening up new possibilities for modeling investment strategies considering various economic indicators and global trends.